Ethereum Smart Contracts for Educational Certificates - Dias , Emanuel Filipe Gomes (2018)
Since blockchains started making its steps for recognition to the world, it began achieving new forms of entries in the daily life, a simple example is the way society trade with virtual coins - cryptocurrency. By this definition, the education fields can take advantage of this flexible system to ensure the recognition’s work of the scholar. With the ability of students getting credit for the knowledge that happens anywhere, not just in schools or formal classes, to be certificated in the blockchain so it answers all sorts of manners of availability and validation. This work is prompted to demonstrate how the smart contracts transactions can be used in learning areas, to historically maintain educational certified documents on the blockchain. In such way, the investigation of the Ethereum’s blockchain is taken into consideration, to obtain an essential overview of the functionalities that allow to create a prototype, for the certificate management between entities.